Alliances, Nuclear Weapons and Escalation Managing Deterrence in the 21st Century - Frühling, Stephan; O'Neil, Andrew (ANU Press, 2021)
In an era of great power competition, the role of alliances in managing escalation of conflict has acquired renewed importance. Nuclear weapons remain the ultimate means for deterrence and controlling escalation, and are central to US alliances in Europe and the Indo-Pacific. However, allies themselves need to better prepare for managing escalation in an increasingly challenging geostrategic and technological environment for the US and its allies. While the challenge of great power competition is acute at both ends of Eurasia, adversary threats, geography and the institutional context of US alliances differ. This book brings together leading experts from Europe, Northeast Asia, the United States and Australia to focus on these challenges, identify commonalities and differences across regions, and pinpoint ways to collectively manage nuclear deterrence and potential escalation pathways in America's 21st century alliances.